Seasonal prevalence of the insect pathogenic fungus Colletotrichum nymphaeae in Brazilian citrus groves under different chemical pesticide regimes. (August 2016) - Mascarin, Gabriel Moura; Guarín-Molina, Juan Humberto; Arthurs, Steven Paul; Humber, Richard Alan; Moral, Rafael de Andrade; Demétrio, Clarice Garcia Borges; Delalibera, Ítalo
Abstract: We report an endemic entomopathogenic fungus, known in Brazil as the 'salmão' fungus and identified here as Colletotrichum nymphaeae (Sordariomycetes: Glomerellales), infecting populations of citrus orthezia scale, Praelongorthezia praelonga . The seasonal prevalence of this pathogen in P . praelonga populations was investigated in three commercial citrus groves maintained under different pesticide regimes. Two citrus groves included inundative releases of another insect pathogenic fungus, Lecanicillium longisporum . Natural epizootics were consistently observed, with up to 84% infection rates being recorded during the warm rainy season. Temporal progression of C . nymphaeae -induced disease varied among the three pesticide regimes. Low infection levels from C . nymphaeae were associated with intensive application of broad spectrum pesticides. However, the prevalence of C . nymphaeae followed a density-dependent pattern with insect host abundance, irrespective of the pesticide regime. High proportions of Lecanicillium -infected insects were observed following infection peaks of C . nymphaeae and both fungi together contributed to 95% overall mortality of citrus orthezia during the wet season. Hence, the combined effect of both fungi considerably improves the biological control of citrus orthezia. We also surmise that the host abundance, environmental conditions, and application frequency of chemical pesticides in citrus groves exert a great influence in the seasonal prevalence of C . nymphaeae -induced disease. Altogether, these results suggest that C . nymphaeae is an important pathogen of P . praelonga and indicate that frequent use of synthetic pesticides may delay or reduce fungal epizootics. Graphical abstract: Highlights: The 'salmão fungus' was identified as Colletotrichum nymphaeae . C . nymphaeae is an important natural enemy of citrus orthezia. Outbreaks of C . nymphaeae were density dependent and followed seasonal trends. We observed highest C . nymphaeae prevalence during rainy and warmer conditions. We observed lowest C . nymphaeae prevalence in grove receiving more frequent pesticide applications.